More is not necessarily better: An empirical analysis of the inequality-growth tradeoff using the Luxembourg Income Study - Georges Heinrich (Luxembourg Income Study (LIS), 2003)
Whenever a country experiences an increase in its mean income, inequality roars its ugly head and the net outcome in terms of poverty remains ambiguous. Kakwani (2000) proposes an instrument that allows quantifying this inequality-growth tradeoff. This paper applies that methodology to 28 middle- and high-income countries included in the Luxembourg Income Study database. It finds that the inequality-growth tradeoff is generally quite high for all countries. This finding implies that there can be no sustained reduction of poverty without income redistribution.
Keywords: 330; Wirtschaftswachstum; Einkommensverteilung; Disparitätsmaß; Industrieländer